JAK2/STAT3 pathway mediates beneficial effects of pterostilbene on cardiac contractile and electrical function in the setting of myocardial reperfusion injury - Li, S; Wang, H; Zhou, Y (Physiological research, 2022)
Contractile dysfunction and fatal arrhythmias are the hallmarks of myocardial ischemia/reperfusion (I/R) injury. Pterostilbene has notable cardioprotective effects, but its main mechanisms are not fully understood. Here, we investigated the effect of PTE on myocardial hemodynamics, arrhythmias, inflammatory/oxidative responses, and the causal role of the JAK2/STAT3 pathway in rats with acute myocardial I/R injury. Sixty male 7-8 months Sprague-Dawley rats (n=10/each group) experienced in vivo model of myocardial I/R injury through 40-min LAD coronary artery occlusion and subsequent 24-h reperfusion. PTE at concentrations of 5 and 25 mg/kg was intraperitoneally administered to rats five min before reperfusion. Cardiac hemodynamics, reperfusion-induced ventricular arrhythmias, infarct size, inflammatory cytokines, oxidative stress markers, the activity of the JAK2/STAT3 pathway were measured as the endpoints. Administration of PTE to I/R-injured rats recovered myocardial contractile function and reduced infarct size and ventricular arrhythmias counts and incidence in a dose-dependent manner. PTE at 25 mg/kg significantly and more potently reduced the levels of inflammatory mediators NF-?B, TNF-?, and IL-1?, suppressed intracellular ROS production, augmented the activity of glutathione, and manganese-superoxide dismutase, and upregulated the JAK2 and STAT3 phosphorylation. Importantly, pretreatment of rats with Ag490 as a JAK2 inhibitor significantly abolished the cardioprotective and signaling effects of PTE in I/R rats. PTE exerts significant protective effects on reducing arrhythmias and myocardial infarction and enhancing cardiac function by stimulating JAK2/STAT3-related suppression of inflammatory and oxidative reactions in the I/R injury setting.
Keywords: interleukin-1; apoptóza; stilbeny; Myocardial Reperfusion Injury; mediátory zánětu; reaktivní formy kyslíku; reperfuzní poškození; Glutathione; Superoxide Dismutase; Apoptosis; Inflammation Mediators; Janus kinasa 2; Stilbenes; cytokiny; krysa rodu Rattus; potkani Sprague-Dawley; Reperfusion Injury; infarkt myokardu; Interleukin-1; Myocardial Infarction; Cytokines; Manganese; Janus Kinase 2; reperfuzní poškození myokardu; Rats, Sprague-Dawley; mangan; mužské pohlaví; superoxiddismutasa; zvířata; glutathion; Rats; Animals; Reactive Oxygen Species; Male